2020
DOI: 10.1111/jvim.15708
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and quantitative analysis of acid‐base and electrolyte imbalances in horses competing in cross‐country competitions at 2‐star to 5‐star level

Abstract: Background Early recognition and management of acid‐base, fluid, and electrolyte disorders are crucial for the maintenance of health and performance in equine athletes. Objectives To analyze changes in acid‐base and electrolyte status associated with exercise during cross‐country competitions at different levels using traditional and quantitative approaches. Animals Thirty‐eight eventing horses. Methods Prospective observational study. Jugular venous blood samples were collected before and after the cross‐coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Precision targets were met by the epoc machine for pH, PO 2 , Na + , K + , glucose, lactate, HCO 3 − , BE (ecf) and SO 2 , but not for PCO 2 , iCa 2+, HCT and Hb [ 14 ], while agreement was poor for Hct, Hb and BE when compared to the iSTAT or an ABL machine. Kirsch and co-workers [ 12 ] reported that the epoc was not meeting precision targets for pO 2 , pCO 2 and K + and that agreement was poor for pH, [HCO 3 − ] and [Na + ] when compared with the Cobas analyzer. Despite these variable results for precision and agreement with other machines, the epoc was chosen as a comparison machine for the GEM5000 in the present study, as its precision was generally accepted as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision targets were met by the epoc machine for pH, PO 2 , Na + , K + , glucose, lactate, HCO 3 − , BE (ecf) and SO 2 , but not for PCO 2 , iCa 2+, HCT and Hb [ 14 ], while agreement was poor for Hct, Hb and BE when compared to the iSTAT or an ABL machine. Kirsch and co-workers [ 12 ] reported that the epoc was not meeting precision targets for pO 2 , pCO 2 and K + and that agreement was poor for pH, [HCO 3 − ] and [Na + ] when compared with the Cobas analyzer. Despite these variable results for precision and agreement with other machines, the epoc was chosen as a comparison machine for the GEM5000 in the present study, as its precision was generally accepted as satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…BGEA is especially indicated in patients in whom acid–base or electrolyte imbalances are suspected [ 1 , 2 , 3 ], such as in critically ill patients, where BGEA helps in monitoring patients and guides fluid support according to their needs. Likewise, the use of BGEA has been recommended to monitor exercising horses, as high-intensity exercise is associated with alterations in acid–base and electrolyte balance [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In addition, arterial BGEA can be used to assess ventilation efficiency of the lungs [ 2 ], making it indicated for the monitoring of patients undergoing general anesthesia, patients suffering from cardiac or respiratory disease and critically ill foals [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have applied Stewart’s physicochemical approach to acid-base analysis in exercising horses [ 10 , 11 , 12 , 13 , 39 , 47 ], as well as descriptive acid-base studies [ 4 , 5 , 48 , 49 ] have not applied temperature adjustments. High intensity exercise in horses results in large increases in core and peripheral temperatures [ 33 , 49 , 50 , 51 ], with core temperatures in excess of 43 °C reported at the end of high intensity exercise conducted in hot, humid conditions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A third limitation is that temperature adjustments were applied using core body (PA) temperature, while temperatures in contracting muscles at the end of exercise approached 43 °C while peripheral temperatures only approached 39 °C [ 39 ]. Measurement variability can make it difficult to identify clear responses when the physicochemical approach is applied to small groups of animals because of the animal variability, in contrast to when the approach is used with individuals [ 13 , 28 ]. The animal variability reflects both the number of individual plasma variables that change as well as differences in strategies used to control each of the plasma variables over time [ 28 ].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation